Oesophageal Atresia - Experience of 7 Years with Data Evaluation (Medical Forum Monthly, 2024)
Objective: Study conducted for evaluation of Oesophageal atresia patients to assess the factors influencing the survival and outcome. Design of Study: Prospective analytical study. Place & Duration of Study: This study was conducted in dept. of Paediatric surgery at peoples medical college, Nawabshah. from September 2001 to September 2008. Patients and Methods: A prospective analysis of 37 cases of Oesophageal Atresia (EA) was performed. In this study, 37 neonates were admitted with the diagnosis of EA with or without TEF .The data were collected retrospectively from hospital charts. The preoperative assessment of upper pouch was done with plain X-ray chest with 8 Fr Red Rubber catheter. The associated congenital anomalies were evaluated on the basis of careful examination, radiological and sonological investigations. Results: The commonest type of Oesophageal Atresia was with distal Tracheoesophageal Fistula (TEF) in 32 cases (86.48 %). Associated anomalies were present in 50% patients, cardiac was commonest followed by gastrointestinal anomalies. Vacterl association was found in 6 (16.21 %) cases. Prematurity, associated congenital anomalies, gap between esophageal ends and preoperative respiratory status were the significant factors affecting the survival. Primary extra pleural repair was the surgical approach in most of the patients except two with difficulty that change to intra pleural approach. Retro pleural drainage was used in 32 classical type 1 cases. Staged procedures were performed in 5 cases of isolated Oesophageal Atresia. Pneumonitis and sepsis were the most common early postoperative complications (30%). Sepsis and cardio respiratory arrest were the most common causes of mortality 11 cases (18.91). Oesophageal leak found in 3 cases, including 2 major and 1 minor leaks. Major leak followed by sepsis caused 1 Deaths. Survival as per Waterston criteria was 85% in group A, 66.6% in group B and 20% in group C. Conclusion: Factors affecting the survival of patients with Oesophageal Atresia are major or life-threatening associated anomalies, long gap, pneumonia and sepsis at presentation or that acquired during hospitalization and major leaks. The high incidence of low birth weight, delayed diagnosis, poor referral, low-socio economic status and lack of advanced neonatological back up are important contributory factors to poor outcome.